The geology of the Krantzberg tungsten deposists, Omaruru, South West Africa - Schlogl, H. U.(Heinz-Ulrich) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1984..